The Mediating Role of Diffuse-Avoidant Identity in the Relationship between Moral Intelligence and Family Functioning with Addiction Potentials of Male Adolescents - Hosseinpour, Shahrzad; Alizadeh, Marjan; Homaei, Rezvan (Archives of Men's Health, 2023)
Introduction: Substance abuse is a major psychosocial disorder that causes irreparable physical and mental damage based on the different personal, social, and personality characteristics of each person. We aimed to investigate the mediating role of diffuse-avoidant identity in the relationship between moral intelligence and family functioning with addiction potentials of male adolescents. Materials and Methods: In this descriptive-correlational study, multistage cluster sampling was used to enroll 315 individuals among all male adolescents studying in Tehran, Iran, in 2021. The research instruments included the Addiction Potential Scale (APS), the Moral Intelligence Questionnaire (MIQ), the Family Assessment Device (FAD), and the Identity Style Inventory (ISI). The proposed model was assessed using structural equation modeling (SEM), and indirect relationships were examined using the bootstrapping method. Results: The results revealed that addiction potentials significantly and negatively correlated with moral intelligence and family functioning. Moreover, addiction potentials significantly and positively correlated with diffuse-avoidant identity (P<0.01). The direct paths from all variables (except that from family functioning) to addiction potential were significant (P<0.01). Also, diffuse-avoidant identity meditated the relationships of moral intelligence and family functioning with addiction potential (P<0.01). Conclusion: The proposed model fitted the data well; therefore, the results considerably improved our understanding of factors affecting addiction potential among male adolescents.